2020
DOI: 10.1126/sciadv.aax5331
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing hydrogenation activity of Ni-Mo sulfide hydrodesulfurization catalysts

Abstract: Unsupported Ni-Mo sulfides have been hydrothermally synthesized and purified by HCl leaching to remove Ni sulfides. Unblocking of active sites by leaching significantly increases the catalytic activity for dibenzothiophene hydrodesulfurization. The site-specific rates of both direct (hydrogenolytic) and hydrogenative desulfurization routes on these active sites that consist of coordinatively unsaturated Ni and sulfhydryl groups were identical for all unsupported sulfides. The hydrogenative desulfurization rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 54 publications
(52 reference statements)
0
35
0
Order By: Relevance
“…The accessible NiS x sites are removable while the internal NiS x sites are not (Figure ). However, in our opinion, the efficiency of acid leaching on the supported catalysts (e.g., NiMoS/Al 2 O 3 ) would be relatively tricky because the stability and properties of supports need to be concerned during acid treatment. Despite NiS x and CoS x being inactive in promoting HDS, they could involve the synergism with active phases via hydrogen spillover.…”
Section: Description Of Hds and Industrial Hds Catalystsmentioning
confidence: 97%
See 1 more Smart Citation
“…The accessible NiS x sites are removable while the internal NiS x sites are not (Figure ). However, in our opinion, the efficiency of acid leaching on the supported catalysts (e.g., NiMoS/Al 2 O 3 ) would be relatively tricky because the stability and properties of supports need to be concerned during acid treatment. Despite NiS x and CoS x being inactive in promoting HDS, they could involve the synergism with active phases via hydrogen spillover.…”
Section: Description Of Hds and Industrial Hds Catalystsmentioning
confidence: 97%
“…(c) Cross section after leaching (inset: SEM image of NiMo-3 showing only the MoS 2 rods after leaching). Reproduced with permission from ref . Copyright 2020 AAAS publications.…”
Section: Description Of Hds and Industrial Hds Catalystsmentioning
confidence: 99%
“…In a study by Subbaraman et al, it is stated that Ni 2+ is more active than other divalent cations (Co 2+ , Fe 3+ , Mn 2+ ), and this is ascribed to the enhanced 3d–2p repulsion between the d-band of the metal and p-band of the coordinated electronegative ligand (S 2– ). Another example is Al 2 O 3 -supported M–Mo–S (M = Co or Ni), in which the second metal atoms are generally located at the edges of MoS 2 . It is found that Co or Ni plays the role of an electron donor to Mo atoms, weakening the bond of Mo–S, and consequently producing S vacancy sites which play a key role in hydrodesulfurization processes.…”
Section: Properties Of Metal Phosphides and Sulfidesmentioning
confidence: 99%
“…The introduction of metal oxides as supports which investigated the catalytic activities of the sulphided CoMo catalysts and their consequent dependence on the nature of the support and additives incorporation is not new [91]. Many materials have been employed as supports for HDS catalysts [43,92], having acidic or basic sites such as carbon, alumina, mixed oxides, and porous materials. The most applicable ones reported so far include Al 2 O 3 , SiO 2 , ZrO 2 , TiO 2 , MgO, as well as mixed oxides among others [45].…”
Section: Support For Metallic Compositesmentioning
confidence: 99%